THE INFLUENCE OF GROSS DOMESTIC PRODUCT, IMPORTS AND THE EXCHANGE RATE ON FOREIGN EXCHANGE RESERVES IN INDONESIA - Zulfikar, Zulfikar; Syafira, Syarifah (LPPM Universitas Malikussaleh, 2024)
This research aims to analyze the influence of gross domestic product, imports and the exchange rate on foreign exchange reserves in Indonesia in the short and long term. This research uses secondary data obtained from World Bank publications for 32 years (1991-2022). To achieve the results of this research, Autoregressive Distributed Lag (ARDL) dynamic model analysis was used using the Eviews program. The results of this research in the short term show that the gross domestic product variable has a positive and insignificant effect, imports have a negative and insignificant effect, while the exchange rate has a positive and significant effect on foreign exchange reserves. In the long term, the results of this research show that the gross domestic product and exchange rate variables have a positive and significant effect on foreign exchange reserves, while imports have a negative and significant effect on foreign exchange reserves in Indonesia.